Exponential and logarithm of multivector in low-dimensional (n = p + q < 3) Clifford algebras - Dargys, Adolfas; Acus, Artūras (Nonlinear Analysis: Modelling and Control, 2022)
The aim of the paper is to give a uniform picture of complex, hyperbolic, and quaternion algebras from a perspective of the applied Clifford geometric algebra. Closed form expressions for a multivector exponential and logarithm are presented in real geometric algebras Clp;q when n = p + q = 1 (complex and hyperbolic numbers) and n = 2 (Hamilton, split, and conectorine quaternions). Starting from Cl0;1 and Cl1;0 algebras wherein square of a basis vector is either –1 or +1, we have generalized exponential and logarithm formulas to 2D quaternionic algebras Cl0;2, Cl1;1, and Cl2;0. The sectors in the multivector coefficient space, where 2D logarithm exists are found. They are related with a square root of the multivector.
Keywords: Clifford (geometric) algebra; exponential and logarithm of Clifford numbers; quaternions